Apology of the Adventurer. José Carlos Mariátegui, by Guido Podestá Airaldi - Gonzales Alvarado, Osmar (2021)
This article is a review of Guido Podestá Airaldi's voluminous book, Apología del aventurero. José Carlos Mariátegui, by Guido Podestá Airaldi, which allows us to dive into Mariátegui's cultural facet. This is done without the pretentious erudition of the bibliomaniac, but with the pedagogical knowledge of the researcher who seeks in each aspect and topic discussed to propose new interpretations on the most important ideologist that Peru has given to the world. There are many other topics that Podestá unfolds in this book that is called to become fundamental in all study on José Carlos Mariátegui: as the effect that the Italian experience caused in our thinker; moreover, how he analyzed Italy itself and the politics; the relationships that he established with his contemporaries; how he positioned himself in front of the oligarchic political system. In short, an essential reading for the hermeneuts of Mariátegui's life and work.